Testicular cancer among US men aged 50 years and older. (August 2018) - Ghazarian, Armen A.; Rusner, Carsten; Trabert, Britton; Braunlin, Megan; McGlynn, Katherine A.; Stang, Andreas
Highlights: Between 1999–2014, TGCT incidence rates increased among US men aged ≥ 50 years, with greater increases observed for nonseminoma than seminoma. Incidence rates for spermatocytic tumors and non-germ cell tumors (testicular lymphoma, sex cord-stromal tumors) remained relatively unchanged during the time period. The incidence of spermatocytic tumors, sex cord-stromal tumors, and testicular lymphoma increased steadily with age in contrast to rates of seminoma and nonseminoma, which steadily declined with age. Given the distinct time-trends and age-specific patterns of testicular cancer in men aged 50 years and older, additional investigation of risk factors for these tumors is warranted. Abstract: Background: The incidence of testicular cancer in the United States (US) has substantially increased in recent decades. The majority of testicular cancers are germ cell tumors (TGCT), which are the most commonly occurring malignancies among men aged 15–44 years in the US. To date, few studies have focused on testicular cancer among men aged ≥ 50 years. Thus, we sought to examine detailed descriptive features, including incidence rates and age patterns, of tumors that arise in the testes among men aged ≥ 50 years. Methods: Data from forty-one US cancer registries were included for the years 1999–2014. Incidence rates per 100, 000 person-years and their 95% confidence intervals (CI) were calculated by race/ethnicity, histology, and age at diagnosis. Estimates of annual percent change (APC) were also calculated. Results: Age-specific incidence rates of spermatocytic tumors, sex cord stromal tumors and lymphomas rose with age, while age-specific incidence rates of seminomas and nonseminomas declined. Between 1999 and 2014, the incidence of nonseminoma (APC = 3.26, 95% CI: 2.27–4.25) increased more than any other tumor type. The incidence of seminoma (APC: 1.15, 95% CI: 0.59–1.71) also increased, while rates of testicular lymphoma (APC: −0.66, 95% CI: −1.16 to −0.16), spermatocytic tumors (APC: 0.42, 95% CI: −1.42 to 2.29), and sex cord stromal tumors (APC: 0.60, 95% CI: −3.21 to 4.55) remained relatively unchanged. Conclusion: Given the distinct time-trends and age-specific patterns of testicular cancer in men aged ≥50 years, additional investigation of risk factors for these tumors is warranted.